2017
DOI: 10.4236/jbbs.2017.73012
|View full text |Cite
|
Sign up to set email alerts
|

Light Pollution Associated with Delayed Sleep Time: A Major Hygienic Problem in Saudi Arabia

Abstract: Background: It was well established that exposure to nighttime light was responsible of a diverse negative health effect. Therefore, the aim of this study was to assess the epidemiologic exposure to artificial light at night time and negative health consequences that associated with prolonged nighttime lighting exposure. Methodology: This is a cross-sectional survey, involving a total of 266 Saudi residents living in the city of Hail, Northern KSA. Essential information regarding exposure to light at night tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…It is interesting to note that the average amount of sleep that college students get around the world ranges anywhere from 6.4 to 8 h per night (e.g., Sweileh et al, 2011). It is also interesting to note that estimates for Saudi college students are exactly at the low bound estimate of 6.4 h that is reported in the international literature (Ahmed et al, 2017). Al-Hazzaa et al (2012) indicated that similar quantities were found in Saudi Arabian adolescents between the ages of 15 and 19 years old.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…It is interesting to note that the average amount of sleep that college students get around the world ranges anywhere from 6.4 to 8 h per night (e.g., Sweileh et al, 2011). It is also interesting to note that estimates for Saudi college students are exactly at the low bound estimate of 6.4 h that is reported in the international literature (Ahmed et al, 2017). Al-Hazzaa et al (2012) indicated that similar quantities were found in Saudi Arabian adolescents between the ages of 15 and 19 years old.…”
Section: Introductionmentioning
confidence: 81%
“…There are questions about whether these results would hold true in the Kingdom of Saudi Arabia despite the overwhelming empirical evidence in favor of morning testing in the international literature, which is partly driven by a “circadian preference for daily activities” ( Putilov, 2017 ). According to Önder (2022) , sleep deprivation and the presence of light pollution alone cause a mismatch between the biological and social rhythm when a late-night nap is taken when an early wake-up is necessary ( Ahmed et al, 2017 ). Consequently, for students in Saudi Arabia early class attendance and morning testing may suffer for reasons discussed next.…”
Section: Introductionmentioning
confidence: 99%